Teaching Procedure Text By Using Interactive Activities To Improve The Speaking Ability Of The Students - Dwisnu, Erlian (Jurnal Pendidikan Rafflesia, 2023)
The objectives of this research were to find out the significant improvement speaking ability by using interactive activities and to find out the students’ perception about the use of interactive activities. This study used qualitative descriptive method as classroom action research as the design of the study. The samples of this study were the ninth grade students of SMP N 03 Lebong Tengah. Significant improvement of English speaking ability by using interactive activities and improvement of the students’ perception about the use of interactive activities. It means that the use of interactive activities is more effective than conventional active learning strategy, especially on speaking than reading based on the result. Clearly, from the result, it can be said that there was significant improvement of English speaking and reading achievement by using the interactive activities.